The Effectiveness of Group Counseling Services in Handling Student Indiscipline in Grade XI at Ambon Rehoboth Christian High School - Tiur Latupeirissa; Winny Cristi Loupatty; Syaloomita Ester Soumahu (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to uncover and describe various forms of student behavior that indicate a lack of discipline among grade XI students of Rehoboth Christian High School, as well as to explain in depth how the process of implementing group counseling services is carried out in overcoming this undisciplined behavior. The background of this study is rooted in the emerging discipline problems, especially those involving students from Negeri Kariuw, who are victims of social conflicts that occur in their home areas. In its implementation, this study uses a descriptive approach with qualitative methods, while data collection techniques are carried out through in-depth interviews, direct observation, and documentation of various relevant sources. The subjects of this study consisted of five grade XI students, a guidance and counseling (BK) teacher, one homeroom teacher, and one vice principal who has a role in supervising students. The results of the study showed that undisciplined behavior found included students being late to school, non-compliance with applicable dress codes, and violations of the rules and norms set by the school. Through the implementation of group counseling services, it is proven that students get space to speak openly, receive emotional support, and strengthen their understanding of the importance of discipline through interactions that occur among group members. Based on the results obtained, it can be concluded that group counseling services are effective in helping to suppress undisciplined behavior and also encourage the formation of positive attitudes and student responsibility towards the rules that apply in the school environment. Keywords: Group counseling, student indiscipline, guidance counseling